Evaluasi Penggunaan Obat Triheksifenidil Sebagai Terapi Adjuvan Pada Pasien Fangguan Afektif Bipolar Di Rumah Sakit Jiwa Provinsi Jawa Barat - Cantika, Erika; Putri, Fitria Sulistia; Purwaeni, Purwaeni; S, Encep; Nur, Ice Laila (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2025)
Background: Bipolar affective disorder is a mental disorder that attacks the psychological condition, characterized by mood swings in the form of mania and depression. The high number of mental health cases in Indonesia is one of the challenges of treatment, especially in the pharmaceutical world. Evaluation of drug use is a structured quality assurance program, and provides assurance that the drugs given are appropriate, safe, and effective. Objective: This study aims to evaluate the use of trihexyphenidyl in patients with bipolar affective disorder at the West Java Provincial Mental Hospital. Methods: The research design used was a retrospective observational study with a descriptive cross-sectional approach. The data source used in the study was written information in the medical records of mental patients diagnosed with bipolar affective disorder who received trihexyphenidyl drug therapy at the West Java Provincial Mental Hospital. Results: Based on the results of the study, 93 patients diagnosed with bipolar affective disorder using trihexyphenidyl were obtained, the results of the ANOVA test on the evaluation of drug use showed a significance value of 0.021 <0.05 so that it can be concluded that the data has differences from the research variables. Conclusion: Based on the results of the study, it can be concluded that the evaluation of the use of trihexyphenidyl drugs in patients with bipolar affective disorder is appropriate and in accordance with the rationality of drug use.